Effet Combin Des Financements Extrieurs Sue La Croissance Economique En Afrique Subsaharienne (Global Journal of Management and Business Research, 2017)
The purpose of present paper is to determinate combined effect of external funding: official development assistance (oda), workers’ remittances (wr) and foreign direct investment (fdi) on economic growth in sub-saharan africa (ssa). With a dynamic panel of twenty-three ssa countries, from 1985 to 2014, economic growth equation integrating external funding is estimated thanks to the generalized method of moments (gmm) system from blundel and bond (1998). The results of the analysis show that external funding, individually or combined does not contribute to economic growth in ssa.
Keywords: external funding; ODA; WR; FDI; economic growth; SSA